PENGETAHUAN IBU YANG MEMPUNYAI BAYI TENTANG DAMPAK PEMBERIAN SUSU FORMULA DI KELURAHAN SIHITANG KECAMATAN PADANGSIDIMPUAN TENGGARA - FATIMAH . (LP2MTBM MAKARIOZ, 2021)
This research was conducted using a descriptive method using a total sampling of 30 respondents, which was examinedbased on knowledge, age, education, occupation, parity, and information sources. Based on the research results, it is knownthat the majority of respondents with less knowledge are 18 respondents (60%), the majority of respondents with lessknowledge are 20-40 years old (40%). The majority of respondents with less knowledge based on junior high schooleducation were 15 respondents (50%), the majority of respondents with less knowledge of the work of IRT were 11respondents (36.67%), the majority of respondents with less knowledge based on parity grandepara 9 respondents (30%),the majority of respondents with less knowledge obtained sources of information from electronic media were 10 respondents(33.33%). Based on the results of the study, it can be concluded that the majority of the knowledge of mothers who havebabies about the impact of formula feeding is still lacking, so it is hoped that mothers who have babies will follow thecounseling so that the mother's knowledge of the impact of formula feeding increases.